2016
DOI: 10.1080/02688697.2016.1220502
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and posterior spinal fat content: impact on complications in non-complex lumbar spine surgery

Abstract: Obesity and posterior spinal fat content correlate with the length of stay in simple spine surgery. There is a non-significant trend towards increased non-operative complications in overweight and obese patients, which could reach significance with larger numbers and prospective data. Excess posterior spinal fat is not associated with increased operative complications, operating time or blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Single-center retrospective studies with smaller cohorts have found similar results 28,29,32–34 . Grover et al 35 found that obesity and posterior spinal fat content positively correlate with LOS. Using Marketscan data, our study adds to the growing body of data that patients with obesity experience a higher incidence of postoperative complications (Table 2) and increased LOS, revision rate, and readmission rate (Table 3).…”
Section: Discussionmentioning
confidence: 72%
“…Single-center retrospective studies with smaller cohorts have found similar results 28,29,32–34 . Grover et al 35 found that obesity and posterior spinal fat content positively correlate with LOS. Using Marketscan data, our study adds to the growing body of data that patients with obesity experience a higher incidence of postoperative complications (Table 2) and increased LOS, revision rate, and readmission rate (Table 3).…”
Section: Discussionmentioning
confidence: 72%
“…Specifically, 729 papers were duplicated, while 732 articles were found to have irrelevant title. Moreover, 45 articles were excluded after reading since they did not meet the inclusion 124 Retrospective study 2 Kukreja et al, 2015 51 Retrospective study 2 Lingutla et al, 2015 30 Meta-analysis 1 Nota SP et al, 2015 125 Retrospective study 2 Ou et al, 2015 10 Retrospective study 2 Planchard RF et al, 2015 126 Retrospective study 2 Retrospective study 2 96 Mcclendon et al, 2014 16 Retrospective study 2 97 McGuire KJ et al, 2014 132 Prospective study 1 98 Pereira BJ et al, 2014 133 Retrospective study 2 99 Quah C et al, 2014 134 Retrospective study 2 100 Seicean A et al, 2014 135 Retrospective cohort study 3 101 Srinivasan et al, 2014 136 Retrospective study 2 102 Terman et al, 2014 28 Retrospective cohort study 3 103 Wang J et al, 2014 137 Prospective study 1 104 Lau, Khan et al, 2013 27 Retrospective study 2 105 Lau, Ziewacz et al, 2013 52 Retrospective study 2 106 Rihn JA et al, 2013 138 Retrospective study 2 107 Rosenfeld HE et al, 2013 139 Case series 4 108 Gaudelli C et al, 2012 140 Retrospective cohort study 3 109 Kalanithi et al, 2012 17 Retrospective study 2 110 Mehta AI et al, 2012 141 Retrospective study 2 111…”
Section: Resultsmentioning
confidence: 99%
“…While outcomes are reported to be satisfactory and often comparable among obese and nonobese patients treated with surgery when needed, peri-operative complications rate seems to be higher in most of the analyzed papers with few exceptions ( Table 3 ). 60 , 62 , 63 , 65 , 66 , 70 , 73 , 77 , 78 , 80 , 82 , 86 , 88 , 90 , 92 - 94 , 97 , 101 , 102 , 105 , 107 , 109 - 112 , 114 , 116 , 118 , 123 , 125 , 126 , 129 , 131 , 133 , 135 , 139 - 141 , 146 - 148 , 151 - 153 , 166 -...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation